2007
DOI: 10.1303/aez.2007.247
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Japanese isolates of the pinewood nematode, Bursaphelenchus xylophilus (Aphelenchida: Aphelenchoididae), at heat-shock protein 70A lucus and the field detection of polymorphic populations

Abstract: Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) pattern of heat-shock protein 70A gene (hsp70A) was examined for 29 isolates of the pinewood nematode. Among them, two known avirulent and five virulent isolates generated banding patterns identical within each of the two isolate groups but distinctive between the two. On the other hand, field populations were collected in two geographical areas, around Kasama City, Ibaraki Prefecture and the southern part of Kujukurihama coast, Chib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The variable locus is at the third position of the genetic code and it does not cause any change of amino acid. An interesting result is that all Chinese samples (from different regions) were G at this locus, the same as the Japanese samples reported by Takemoto and his associates [22] . While most of American samples are A, except for few samples mixed with G at this locus.…”
Section: Molecular Mechanisms For the Ecological Adaptation Of B Xylsupporting
confidence: 85%
“…The variable locus is at the third position of the genetic code and it does not cause any change of amino acid. An interesting result is that all Chinese samples (from different regions) were G at this locus, the same as the Japanese samples reported by Takemoto and his associates [22] . While most of American samples are A, except for few samples mixed with G at this locus.…”
Section: Molecular Mechanisms For the Ecological Adaptation Of B Xylsupporting
confidence: 85%
“…Iwahori et al (13) and Takemoto and Futai (30) suggested that Japanese virulent and avirulent isolates of B. xylophilus have different origins, because both isolates are distinguishable from sequences of the internal transcribed spacer of ribosomal DNA (2,13) or heat-shock protein 70A gene (30). This means that genetic polymorphism is present in Japanese nematode populations.…”
Section: Discussionmentioning
confidence: 99%
“…François et al (2007) reported a real-time PCR assay which can detect the limit of 1 pg of nematode DNA because of multiple gene copies of satellite DNA present within a single genome. As well as the topoisomerase I gene, HSP70 also has been used as a target of RFLP analysis and PCR detection of B. xylophilus (Takemoto et al 2005;Leal et al 2005Leal et al , 2007Takemoto and Futai 2007). It is evident that recent progress in nematode genome sequencing and expressed sequence tag (EST) projects (Kikuchi et al 2007) will give more promising and reliable gene candidates for diagnostic developments.…”
Section: Discussionmentioning
confidence: 99%